REFORMULASI SISTEM PERENCANAAN PEMBANGUNAN NASIONAL MODEL GARIS-GARIS BESAR HALUAN NEGARA - Imam Mahdi (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2017)
Abstract: Proconsidering of the need or not GBHN post amendment UUD NRI Year 1945 continue rolling especially when the MPRI in various opportunities to campaign need to reshape GBHN. This is due to several factors, among others: The constitution of Indonesia does not adhere to linear understanding, so that development must be planned through one state direction, that the name of legal products for the direction of the state of Indonesia has not been fixed and always changing. “In the era of President Soekarno’s government the outlines of the state’s bow were given the name of the Planning of the Universe. This means that in the beginning the name of the country’s bow is not GBHN. GBHN is just a naming option in the New Order government. In the reform era called the SPPN, “so since 1960 until now Indonesia actually already has the law for the state direction although the official name is always changing. Therefore, the question of whether the GBHN or the other is not a problem, but the constitutionally the State must have a fixed guideline or guidance to carry out its development.Keywords: GBHN, ontology planning, development and budgeting